2012
DOI: 10.1002/hep.26013
|View full text |Cite
|
Sign up to set email alerts
|

Activated tumor-infiltrating CD4+ regulatory T cells restrain antitumor immunity in patients with primary or metastatic liver cancer

Abstract: The mechanisms that enable liver cancer to escape elimination by the immune system remain unclear, but their elucidation may provide novel therapeutic interventions. We investigated the influence of tumor-infiltrating regulatory T cells on tumor-specific T cell responses in patients with liver cancer, using ex vivo isolated cells from individuals with hepatocellular carcinoma (HCC) or liver metastases from colorectal cancer (LM-CRC). Here we report that in both HCC and LM-CRC, CD41CD251Foxp31 regulatory T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 33 publications
5
147
0
Order By: Relevance
“…As a consequence, tumor-infiltrating Treg, 40 , 41 type 1 regulatory T cells 52 and probably other types of immune suppressor cells were also present in these assays. Therefore, the reported functional effects of checkpoint inhibitors on effector T cells in these assays may be partly indirect, mediated by effects of these antibodies on suppressor cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a consequence, tumor-infiltrating Treg, 40 , 41 type 1 regulatory T cells 52 and probably other types of immune suppressor cells were also present in these assays. Therefore, the reported functional effects of checkpoint inhibitors on effector T cells in these assays may be partly indirect, mediated by effects of these antibodies on suppressor cells.…”
Section: Discussionmentioning
confidence: 91%
“…35 Moreover, the unique immune environment in the liver 36 favors immunological tolerance, 36 and one of the mechanisms used by the liver to resist immune responses is the induction of expression of inhibitory receptors on hepatic T cells 37 , 38 and their ligands on hepatocytes and other liver tissue cells. 39 Previously we have observed that intra-tumoral CD8 + cytotoxic T cells (CTL) and CD4 + T helper cells (Th) are functionally compromised in LM-CRC, 40 and we also demonstrated that the suppression mediated by intra-tumoral regulatory T cells (Treg) in LM-CRC can be alleviated by blocking the inhibitory receptor CTLA4 and activating the stimulatory receptor GITR. 41 However, the expression and functional roles of inhibitory receptor-ligand pathways in regulating tumor-infiltrating effector T cell responses have not been studied yet in LM-CRC.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…10,11 In support of this we and others have described the presence of regulatory CD4 C Foxp3 C T cells in liver tumors, that suppress local antitumor immunity and that are associated with poor patient prognosis. [12][13][14][15][16] Liver TiTreg are characterized by high expression of glucocorticoidinduced tumor necrosis factor receptor related gene (GITR), CTLA-4 and inducible T cell co-stimulator (ICOS). 12 These molecules are important for the immunosuppressive function of Treg and can be targets for immunotherapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Liver TiTreg are characterized by high expression of glucocorticoidinduced tumor necrosis factor receptor related gene (GITR), CTLA-4 and inducible T cell co-stimulator (ICOS). 12 These molecules are important for the immunosuppressive function of Treg and can be targets for immunotherapeutic interventions. Abrogation of Ti-Treg function may allow the induction of antitumor immunity at the tumor site and improve the outcome of immunotherapy aimed to activate antitumor responses.…”
Section: Introductionmentioning
confidence: 99%